The Influence Use of Social Media on the Learning Motivation of Junior High School Students - Sopian, Aldi; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2022)
The learning process today is in dire need of social media, because it will help students in the communication process and seek insight so that it will foster learning motivation in themselves. This study aims to determine the effect of social media on the learning motivation of junior high school students. In this study using a quantitative approach, quantitative research is research based on calculations using numbers starting from data collection, interpretation of the data, as well as appearance and results. The independent variable is social media and the dependent variable is student learning motivation. The subjects of this study were junior high school students who were taken at random totaling ten students. The data obtained from the google form questionnaire data, the analysis technique uses pre-test and post-test. The results showed that the influence of the use of social media by 66% on students' learning motivation and after the direction and instruction increased to 81%. So the existence of social media greatly affects student learning motivation.